Musculoskeletal symptoms, psychosocial factors and work ability in Brazilian labor justice workers. - Kadri Filho, Fauzi El; São-João, Tha&ıs Moreira; Alexandre, Neusa Maria Costa; de Lucca, Sergio Roberto; Gallasch, Cristiane Helena; Rodrigues, Roberta Cunha Matheus; Cornélio, Marilia Estevam (Work, 2021)
BACKGROUND: The implementation of the electronic judicial process (PJe) in recent years is associated with an increase in workload and stricter control through productivity targets in the Brazilian labor judiciary. OBJECTIVES: To evaluate the relations between musculoskeletal symptoms, psychosocial factors and work ability in civil servants of a labor justice body in the context of the PJe. METHODS: A cross-sectional exploratory study with a quantitative approach involving 449 workers. Sociodemographic, occupational and related data were collected through questionnaires validated in the Brazilian context. Data analysis was conducted by descriptive and inferential statistics: Mann-Whitney test, Spearman's correlation coefficient and multiple linear regression. RESULTS: There was a correlation between musculoskeletal symptoms and psychosocial factors (p < 0.05), as well as between both musculoskeletal symptoms and psychosocial factors with reduced work ability (p < 0.05). The multiple linear regression model pointed to the female gender and the dimensions "demands", "control" and "peer support" as related to the musculoskeletal symptoms. CONCLUSION: We highlight the importance of a broader approach, involving psychosocial factors in preventive actions related to musculoskeletal disorders considering the important relationship with work ability.